The synergistic decarboxylation of glyoxylate and 2-oxoglutarate by an enzyme system from pig-liver mitochondria - Stewart, P. R. (1967)
1. An enzyme system that catalyses a synergistic decarboxylation of glyoxylate and 2-oxoglutarate has been purified from pig-liver mitochondria. 2. The purified system is specific for glyoxylate and 2-oxoglutarate as substrates, although in earlier stages of purification glycine and l-glutamate are also active. 3. The reaction is inhibited strongly by EDTA and N-ethylmaleimide. Substrate analogues, present at concentrations equimolar with respect to the substrates, are not effective as inhibitors. 4. The reaction proceeds in the absence of added cofactors. Magnesium chloride, mercaptoethanol and sucrose stimulate the reaction, and stabilize the activity of the enzyme. 5. The pH optimum of the reaction is 7·0. The K(m) values of glyoxylate and 2-oxoglutarate, at saturating concentration of the corresponding co-substrate, are 16mm and 3·6mm respectively. 6. Isotopic work with specifically labelled [(14)C]glyoxylate and 2-oxo[(14)C]-glutarate suggests that the enzyme system catalyses an initial condensation of glyoxylate and 2-oxoglutarate that results in, or leads to, release of C-1 of both substrates as carbon dioxide. C-2 of glyoxylate and C-5 of 2-oxoglutarate do not appear as carbon dioxide. 7. The stoicheiometry of the reaction is complex. During the initial stages of the reaction, more carbon dioxide is recovered from 2-oxoglutarate than from glyoxylate. Subsequently, there is a disproportionate increase with time of carbon dioxide evolution from the carboxyl group of glyoxylate. The excess of decarboxylation of glyoxylate over 2-oxogluturate is further increased by treatment of reaction products with acid.